When nanoparticles meet biofilms—interactions guiding the environmental fate and accumulation of nanoparticles - Ikuma, Kaoru; Decho, Alan W.; Lau, Boris L. T. (Frontiers in Microbiology, 2015)
Bacteria are essential components of all natural and many engineered systems. The most active fractions of bacteria are now recognized to occur as ‘biofilms’, where cells are attached and surrounded by a secreted matrix of “sticky” extracellular polymeric substances (EPS). Recent investigations have established that significant accumulation of nanoparticles (NPs) occurs in aquatic biofilms. These studies point to the emerging roles of biofilms for influencing partitioning and possibly transformations of NPs in both natural and engineered systems. While attached biofilms are efficient “sponges” for NPs, efforts to elucidate the fundamental mechanisms guiding interactions between NPs and biofilms have just begun. In this mini review, special attention is focused on NP-biofilm interactions within the aquatic environment. We highlight key physical, chemical and biological processes that affect interactions and accumulation of NPs by bacterial biofilms. We posit that these biofilm processes present the likely possibility for unique biological and chemical transformations of NPs. Ultimately, the environmental fate of NPs is influenced by biofilms, and therefore requires a more-in depth understanding of their fundamental properties.